Can Financial Ratios Improve Stock Returns in Manufacturing Companies? - Sugeng Suroso (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
For an investor, investing in the selected securities is undoubtedly expected to provide a rate of return that is by the risks that investors must bear. Objectively, this study aims to determine the effect of profitability ratios, liquidity ratios, leverage ratios, activity ratios, and market ratios on stock returns. This research is expected to add empirical evidence regarding profitability ratios, liquidity ratios, leverage ratios, activity ratios, and market ratios to stock returns. The type of research used in this research is verification research using the Explanatory Survey method using Inferential Statistics research techniques. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sampling technique was purposive sampling, based on the specified criteria to obtain a sample of 62 manufacturing companies whose data were by research needs. The research data obtained were analyzed using the Eviews statistical tool. This study finds that the resulting Return on Assets (ROA) will affect the number of dividends distributed. The greater the ratio of net income and total assets, the greater the dividends distributed to shareholders. The Current Ratio cannot be used as a basis for determining investors to buy and sell shares or investments. This study also found that the higher the level of Debt Equity Ratio in a company, the lower the stock returns received by investors in the company, and vice versa. Furthermore, the more significant the company uses its assets to generate total net income, the higher the stock return value. When the Price Book Value increases, the increase in stock returns will also increase.